The Potential of Bioactive Peptides from Animal Protein Sources as a Mental Health Problems Prevention - Nur Hidayah; Sandy Ardiansyah (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
Protein is one of the substances of nutrition macro that is needed by the body are known to contain bioactive peptides. Protein sources can be from vegetables and animals, based on research an animal protein sources more complete, balanced, easily digested and absorbed than vegetable protein sources. Some sources of animal protein (milk, eggs, meat, and products derived and processed) were reported that contain of bioactive peptides. Bioactive peptide has effect as antimicrobial, antithrombotic, antihypertensive, opioid, immunomodulatory, binder minerals, antioxidants, and prevent mental health disorder. The purpose of this paper is to review the peptide bioactive, relationship of mental health with peptide bioactive, and prevention of mental helath problems with bioactive peptide from animal protein sources. Peptides bioactive is an organic substance that is formed by amino acids (2-30 pieces) with the bond of the peptide and the weight of the molecule is small (unit Dalton). Mental health is the condition of the welfare (well-being) of an individual that is aware of its ability to own, can cope with the pressure of life which is normal, can work in a productive and can give a contribution to the community. Peptides bioactive shows such as opioids and inhibit the activity of the enzyme prolyl endopeptidase (PEP, EC 3.4.21.26) that play a role important in the treatment of disorders of the mind because work on the system nerve central (CNS) and can give the effect of a positive on motivation, behavior, stress, control the intake of food or the perception of the sense of pain. Some proteins of animal that has been proven to be able to prevent mental health problems namely, bovine, yogurt, and fresh milk. Still a lot of opportunities in the business of exploration of the source of the protein animal in producing the product peptide bioactive for commercial.